Lawsuits of medicines on a pole municipality of Minas Gerais - Munck, Alice Kappel Roque; Lupatini, Evandro de Oliveira; Pereira, Rouzeli Maria Coelho; Vieira, Rita de Cássia Padula Alves (Journal of Health Care, 2016)
Introduction: The Unified Health System is the medium through which the Brazilian State intends to guarantee all citizens the right to health and pharmaceutical care. However, the claim for medicines in courts has become a noteworthy phenomenon in Brazil, reaching in a significant way the municipalities, the federative entities closest to the citizens. Objective: To study the lawsuits in a pole city of Minas Gerais State. Materials and methods: Documentary and retrospective analysis of the lawsuits filed with drug claims against the city of Juiz de Fora, in 2012 and 2013. Results: The analysis was concentrated on 666 deferred lawsuits with medicine requests against the municipality during 2012 and 2013. It was observed that Juiz de Fora was the municipality of the plaintiff's domicile in 57.7% of the cases. It was found that 62.5% of prescriptions that supported the action came from public health care establishments, 70.9% of the medicines were not part of the cast of any pharmaceutical assistance financing component, and 85% of the 20 most demanded medicines throughout the study were demanded for different therapeutic indications than those of the label directions. Conclusions: Being a regional center for healthcare, Juiz de Fora is driven to extend its services to populations outside the original planning. It is essential to investigate the particularities of judicial demands for medicines in pole cities to ensure that the legalization phenomenon is considered in the planning of healthcare, in the coordination between federal entities, and in healthcare.
Keywords: pharmaceutical services; right to healthcare; medicines